Visualisasi dan Diseminasi Kerangka Induk BS2020 Berbasis Web - Sukron Al Amin; Waris Marsisno (Seminar Nasional Official Statistics, 2021)
The Master Framework of the 2020 Census Block (BS2020) is the result of mapping activities conducted by the Central Statistics Agency (BPS) in 2019. This master framework contains a collection of census blocks in a statistical working area (wilkerstat) with the attributes of load, dominant load, and type of census block. The geographic information system (GIS) used by BPS currently cannot display digital maps down to the smallest unit of analysis level, namely the census block and local environmental unit (SLS). The purpose of this research is to build a web-based BS2020 GIS that has the ability to visualize and disseminate digital maps up to the Census Block and SLS levels. System development is carried out using the Rapid Application Development (RAD) method. The GIS for Visualization and Dissemination of the BS2020 Master Framework has been successfully built. The results of the Black Box testing show that all scenarios have run as expected. Meanwhile, from the user assessment using the Scale Usability System method, a score of 77.95 was obtained which indicates that the system has been functioning and can be well received by users.